The beneficial effects of curcumin supplementation on blood lipid levels among patients with metabolic related diseases in Asia area: a systematic review and meta-analysis of randomized controlled trials - Deng, Zhifang; Yang, Ke; Cai, Xiaonan; Mei, Hong; Xiao, Han; Gao, Wenqi (Frontiers in Sustainable Food Systems, 2023)
Objective Published studies suggest that the effects of curcumin on blood lipids in adults are controversial, and it is unclear whether there is a dose response to lipid changes following curcumin supplementation. Therefore, we conducted a systematic review and meta-analysis of randomized controlled trials (RCTs) to evaluate the effects of curcumin on triglycerides (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL), and high-density lipoprotein cholesterol (HDL) in the Asian populations with metabolic diseases. Methods We systematically searched four electronic databases, including Web of Science, PubMed, Google Scholar, and Cochrane Library, for randomized controlled trials (RCTs) of the effects of curcumin on TG, TC, LDL, and HDL in the Asian populations with metabolic diseases. Mean difference (MD) indicates effect size with combined 95% confidence interval (95% CI). Heterogeneity among studies was assessed by I2. Subgroup analyses were performed to explore potential sources of heterogeneity. Results Evidence from 23 RCTs for TG, 21 RCTs for TC and LDL, and 22 RCTs for HDL showed that curcumin supplementation significantly reduced TG (MD: -18.07 mg/dL, 95% CI: -30.30, -5.85, P < 0. 01), TC (MD:-13.29 mg/dL, 95% CI: -20.43, -6.16, P < 0.01), and LDL (MD: -10.44 mg/dL, 95% CI: -16.87, -4.00, P < 0.01), but no effect on HDL (MD: 1.66 mg/dL, 95% CI: -0.13, 3.44, P = 0.07). In the non-linear dose-response analysis, we observed a significant effect of curcumin supplementation dose on TG levels (P-nonlinearity = 0.022). Conclusion In conclusion, curcumin may be beneficial in reducing TG, TC, and LDL levels in the Asian populations with metabolic diseases. The dose of curcumin intervention may be an underlying factor influencing TG levels.